PENGEMBANGAN MEDIA SIBEBAN UNTUK MENINGKATKAN MOTIVASI SISWA PADA MATERI POTENSI BENCANA ALAM INDONESIA - Purnamasari, Yana Dwi; Wahyuningtyas, Neni (Universitas Islam Sultan Agung, 2025)
The diversity of learning styles of students such as visual, auditory and kinesthetic, is a challenge in learning social studies, especially on the material of Potential Natural Disasters in Indonesia. The mismatch of learning media with student characteristics causes low learning motivation because students have difficulty understanding the concept of material. This research aims to develop metaverse-based SIBEBAN learning media as an innovative solution, using the research and development method (Research & Development) through the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). This media is designed in the form of an interactive virtual museum that presents educational videos, simulative games, visual documentation, articles/news, and LKPD in groups in the form of flipbooks. The implementation results show that this media is able to significantly increase student learning motivation, with an implementation score of 87%. Thus, SIBEBAN media is very feasible and effective in supporting social studies learning that is contextual, fun, and in accordance with the diverse learning needs of students. Suggestions for further research to add individual LKPDs that have been packaged in learning media.